Migraine, Mental Health, and Marginalization: A Study of Psychiatric Comorbidities in a Multiethnic Cohort from Quetta, Pakistan - Kakar, Amanullah; Akbar, Wazir; Kakar, Ainullah; Ahmed, Riaz; Essa, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Migraine is the most common cause of disability in the world, and it often happens along with psychiatric disorders. This study aimed to examine the correlation between migraine and psychiatric comorbidities in Balochistan. Methods: A cross-sectional study involving 349 migraine patients (70.8% female; mean age 38.2 ± 12.5 years) was undertaken from January 2023 to December 2024. Validated instruments (PHQ-9, GAD-7, MIDAS, SF-36) and structured interviews evaluated psychiatric comorbidities, migraine features, disability, and quality of life. Descriptive statistics, bivariate analysis, and logistic regression models determined the predictors of depression and anxiety. Results: Psychiatric comorbidities were frequent, with 44.7% (n = 156) screening positive for depression (PHQ-9 ≥10) and 38.1% (n = 133) for anxiety (GAD-7 ≥10). Patients with chronic migraines demonstrated elevated rates of depression (67.8% vs. 40.0%) and anxiety (61.0% vs. 33.4%) in comparison to those with episodic migraines. Sociodemographic factors, such as illiteracy (51.9%). Logistic model indicated chronic migraine (aOR = 2.8, 95% CI: 1.9–4.0), female gender (aOR = 2.1, 95% CI: 1.4–3.2), illiteracy (aOR = 1.7, 95% CI: 1.1–2.6), and elevated stress (aOR = 3.5, 95% CI: 2.3–5.4) as independent predictors of depression. Patients with comorbidities had 50% reduced SF-36 scores and twice the number of disability days (MIDAS: 12.0 vs. 6.0 days/month). Conclusion: Migraine and psychiatric comorbidities are significantly interconnected, especially among chronic migraine sufferers and socioculturally disadvantaged populations. Research supports the implementation of integrated neurology-psychiatry care models, regular mental health assessments, and culturally customized therapies.